Cameroon : Extension Partnerships with the Private Sector - Trapman, Christopher (2012)
The Cameroon National Agricultural Extension Project is a good practice example of partnership between the government extension service and private agro-input supply companies. The key to success is the ability to leverage the comparative advantage of each party without compromising the efficiency, objectivity or the principles of the extension services. The private suppliers provide new technology while the national extension service shares its experience in testing new technologies with farmers through small-scale demonstration plots.